Dampak Penggunaan Motor Di Desa Mempengaruhi Perubahan Masyarakat & Lingkungan - Ashrul Muhtadi; Bagus Nur Rohman; Andhita Risko Faristiana (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Motorcycle use in villages has increased rapidly and has a significant impact on the social structure of the community. Motorcycles provide better accessibility and mobility for villagers, allowing them to access services and economic opportunities. However, motorcycle use also has a negative impact on the environment, especially in terms of air pollution. Motorcycle engines produce exhaust gases that pollute the air and can adversely affect the health of communities and local ecosystems. Therefore, there is a need for awareness and efforts to manage motorcycle use in villages wisely. This research is expected to provide an understanding for the community regarding the impact of motorcycle use in the village. In writing this journal, the author used qualitative research methods. Primary data in this research was obtained from informants of local residents with an age range of 30-45 years, totaling 20 people. The residents are residents of Menggare, Slahung, Ponorogo. The process of obtaining informants is done by purposive sampling. One of them is by conducting direct interviews. This research is expected to be the basis for mitigating the negative impacts of motorcycle use in the village on the community and the environment